Stereotactic Hypofractionated Irradiation for Metastatic, Inoperable, and Recurrent Malignancies: A Modern Necessity, rather than a Luxury. (25th December 2014) - Susheela, Sridhar P.; Revannasiddaiah, Swaroop; Basavalingaiah, Ajaikumar
Abstract : Stereotactic-irradiation combines highly conformal delivery of radiation to selected volumes at large doses per fraction, with the treatment completed typically within one to five fractions. The radiobiological equivalence of doses delivered by stereotactic-irradiation (often beyond 80–100 Gy) is much higher in comparison to the doses achievable by conventional fractionation. At the high fraction sizes used in stereotactic-irradiation, evidence suggests the role of various radiobiological mechanisms of actions, which are not traditionally relatable with conventional radiotherapy. In spite of the accumulating evidence in favour of the efficacy of stereotactic irradiation in terms of improving local control and at times attaining increments in survival, the clinical adoption of the technique remains dismal. This review provides a brief description of the available evidence describing the benefits of stereotactic-irradiation for the management of patients with oligometastases, unresectable malignancies and for disease recurrence after prior radiotherapy. Given the growing body of evidence illustrating the efficacy of stereotactic irradiation among patients with conditions which were previously often regarded as untreatable, it is likely that the widespread adoption of stereotactic irradiation may achieve cure in a few patients, while in the remainder providing prospects of long term local control. This could be a step in the direction of converting incurable malignancies into chronic controllable diseases.